Diary of a wimpy kid hard luck - Kinney, Jeff (Puffin London, 2015)
Greg Heffley's on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg's life destined to be just another hard-luck story? It is perfect for readers of 8+ and also reluctant readers. You can also discover Greg on the big screen in any one of the three Wimpy Kid Movie box-office smashes. Ages 9+